2009
DOI: 10.2967/jnumed.109.062570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alendronate on Bone Metabolism in Glucocorticoid-Induced Osteoporosis Measured by18F-Fluoride PET: A Prospective Study

Abstract: Osteoporosis represents a significant side effect of glucocorticoid therapy, and alendronate has been reported to prevent this glucocorticoid-induced osteoporosis. Functional imaging with 18 F-fluoride PET allows quantitative analysis of bone metabolism in specific skeletal regions. However, only a few studies have quantitatively determined bone turnover and metabolism in glucocorticoid-induced osteoporosis by radiologic imaging techniques including PET. The aim of this study was to examine changes in regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 36 publications
4
73
1
Order By: Relevance
“…In the only other study we are aware of that used 18 F À PET to examine the regional effects of an osteoporosis therapy, Uchida et al reported a 14% decrease in SUVs at the spine and a 24% decrease at the femoral neck in 24 postmenopausal women treated with alendronate for 12 months for glucocorticoid-induced osteoporosis. (27) In the present study, although there was a highly significant change in 18 F À plasma clearance at the lumbar spine, SUVs at this site were almost unchanged. The 3% increase in SUVs after 6 months of treatment with teriparatide was explained by the 24% increase in spine plasma clearance being almost canceled by a 20% decrease in 18 F À plasma concentration.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In the only other study we are aware of that used 18 F À PET to examine the regional effects of an osteoporosis therapy, Uchida et al reported a 14% decrease in SUVs at the spine and a 24% decrease at the femoral neck in 24 postmenopausal women treated with alendronate for 12 months for glucocorticoid-induced osteoporosis. (27) In the present study, although there was a highly significant change in 18 F À plasma clearance at the lumbar spine, SUVs at this site were almost unchanged. The 3% increase in SUVs after 6 months of treatment with teriparatide was explained by the 24% increase in spine plasma clearance being almost canceled by a 20% decrease in 18 F À plasma concentration.…”
Section: Discussioncontrasting
confidence: 48%
“…An example is the gamma camera method of measuring the skeletal uptake of 99m Tc-methylene diphosphonate ( 99m Tc-MDP) described by Brenner et al (26) For 18 F À PET studies, an equivalent measurement of bone uptake is provided by standardized uptake values (SUVs), which normalize the concentration in the bone region of interest for injected activity and body weight (SUV ¼ mean kBq/ mL x body weight [kg]/injected activity [MBq]). (27) The only previous studies that used 18 F À PET to examine the regional effects of an osteoporosis treatment were a report by Frost et al (21) on the effect of risedronate on bone turnover at the lumbar spine and a study by Uchida et al (27) on the effects of alendronate on bone metabolism at the spine and femoral neck in glucocorticoid-induced osteoporosis. To date, no studies of an anabolic agent have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Zooming in further, in 18 F-Fluoride PET scanning it is believed that PET intensity reflects the activities of osteoblasts and osteoclasts, and at least in animal experiments, microdamage can be detected (147). Regional bone perfusion and turnover studies with bone turnover markers as a reference have been performed comparing different skeletal sites in treatment-naïve and patients with osteoporosis on treatment with various antiosteoporotic agents (148)(149)(150)(151)(152)(153)(154). The long term precision reflected by the coefficients of variation (12.2-26.6%) and intraclass correlation (0.44-0.85) for 18 F-Fluoride PET parameters has been reported to be equivalent to that observed for biochemical bone turnover markers (155).…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…Quant itative radionuclide imaging of the skeleton using 18 F-fluoride PET ( 18 F 2 PET) (1,2) is a valuable tool for research studies examining the pathophysiology of metabolic bone diseases and the response of patients to treatment (3)(4)(5)(6)(7). Treatments for osteoporosis and Paget disease generally have a profound effect on bone remodeling (8)(9)(10)(11), and studies of bone metabolism have an important role in the evaluation of the effect of treatment on bone tissue (12).…”
mentioning
confidence: 99%